2005
DOI: 10.1002/anie.200502484
|View full text |Cite
|
Sign up to set email alerts
|

UN213−: A Structurally Characterized Binary Actinide Heptaazide Anion

Abstract: More stable than it seems: The binary uranium–nitrogen anion U(N3)73− was synthesized and characterized as the (Bu4N)3[U(N3)7] salt. The U(N3)73− ion is the first structurally characterized heptaazide and is the first homoleptic azide of an actinide. The crystal structure shows a pentagonal‐bipyramidal arrangement of the azide ligands around the central uranium(IV) atom (see structure; N: blue; U: green).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 60 publications
8
28
0
Order By: Relevance
“…To the best of our knowledge, no other classes of thorium pseudohalide complexes have been investigated structurally. The existing literature reports of structurally characterised homoleptic actinide pseudohalides consists of five salts containing actinide isothiocyanate anions, namely, Cs 4 U(NCS) 8 3a, (Et 4 N) 4 U(NCS) 8 3b, (Et 4 N) 4 Th(NCS) 8 2a and (Me 4 N) 4 Np(NCS) 8 3c as well as the recently reported heptaazidouranate(IV) anion in (Bu 4 N) 3 U(N 3 ) 7 4. To the best of our knowledge, although actinide isoselenocyanates were previously reported in the literature 5, and several uranium(IV), uranium(VI) and thorium(IV) complexes were prepared and spectroscopically characterised including Th(NCSe) 4 (OP(NMe 2 ) 3 ) 4 5a, none have been unambiguously identified and structurally characterised.…”
Section: Introductionsupporting
confidence: 91%
“…To the best of our knowledge, no other classes of thorium pseudohalide complexes have been investigated structurally. The existing literature reports of structurally characterised homoleptic actinide pseudohalides consists of five salts containing actinide isothiocyanate anions, namely, Cs 4 U(NCS) 8 3a, (Et 4 N) 4 U(NCS) 8 3b, (Et 4 N) 4 Th(NCS) 8 2a and (Me 4 N) 4 Np(NCS) 8 3c as well as the recently reported heptaazidouranate(IV) anion in (Bu 4 N) 3 U(N 3 ) 7 4. To the best of our knowledge, although actinide isoselenocyanates were previously reported in the literature 5, and several uranium(IV), uranium(VI) and thorium(IV) complexes were prepared and spectroscopically characterised including Th(NCSe) 4 (OP(NMe 2 ) 3 ) 4 5a, none have been unambiguously identified and structurally characterised.…”
Section: Introductionsupporting
confidence: 91%
“…Several 24-membered uranium nitrogen rings (UNUN 3 ) 4 have been synthesized by reduction of sodium azide with organometallic metallocene derivatives. In a related development, Margaret-Jane et al reported the synthesis and characterization of an ammonium salt of a uranium polyazide, U(N 3 ) 7 3− [38]. This polyazide is the first structurally characterized heptaazide compound for any element, and it is the first known example of a binary actinide azide compound containing only an actinide metal and azide groups.…”
Section: Novel Uranium-nitrogen Compoundsmentioning
confidence: 99%
“…The formula of the intermediate was assigned in analogy to the recently reported heptaazido complex (Bu 4 N) 3 [U(N 3 ) 7 ] prepared from the reaction of the tetravalent (Bu 4 N) 2 [UCl 6 ] with AgN 3 in acetonitrile. [22] The difference in stability of the two compounds is probably due to the presence of a very different counterion. However, the neutral pyridine adduct [U(N 3 ) 4 (py) 4 ] (2) is sufficiently stable to allow its isolation from pyridine and its crystallographic characterization.…”
mentioning
confidence: 99%